Structural enzymology of Helicobacter pylori methylthioadenosine nucleosidase in the futalosine pathway. (1st January 2014) - Kim, Robbert Q.; Offen, Wendy A.; Davies, Gideon J.; Stubbs, Keith A.
<x xml:space="preserve">Abstract</x> The recently discovered futalosine pathway is a promising target for the development of new antibiotics. The enzymes involved in this pathway are crucial for the biosynthesis of the essential prokaryotic respiratory compound menaquinone, and as the pathway is limited to few bacterial species such as the gastric pathogen Helicobacter pylori it is a potential target for specific antibiotics. In this report, the crystal structure of an H. pylori methylthioadenosine nucleosidase (MTAN; an enzyme with broad specificity and activity towards 6‐amino‐6‐deoxyfutalosine), which is involved in the second step of menaquinone biosynthesis, has been elucidated at a resolution of 1.76 Å and refined with R factors of Rwork = 17% and Rfree = 21%. Activity studies on the wild type and active‐site mutants show that the hydrolysis of 6‐amino‐6‐deoxyfutalosine follows a mechanism similar to that of Escherichia coli MTAN. Further evidence for this mode of action is supplied by the crystal structures of active‐site mutants. Through the use of reaction intermediates, the structures give additional evidence for the previously proposed nucleosidase mechanism. These structures and the confirmed reaction mechanism will provide a structural basis for the design of new inhibitors targeting the futalosine pathway.